2021
DOI: 10.1136/bmjopen-2020-046075
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel ecological analysis of the predictors of spanking across 65 countries

Abstract: ObjectiveEnding violence against children is critical to promote the health and socioemotional development of children across the globe. To this end, the UNICEF and the WHO have called for the abolishment of spanking, which is the most pervasive form of physical violence against children worldwide. This study used an ecological perspective to examine micro-level and macro-level predictors of parental spanking across 65 countries.ParticipantsData came from the fourth and fifth rounds of the UNICEF Multiple Indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 37 publications
(45 reference statements)
4
17
0
Order By: Relevance
“…For instance, understanding children’s cues is a challenge caregivers face in infancy, before children develop language. This perspective is consistent with evidence on the drivers of VAC in Colombia, which indicates that the risk of experiencing VAC varies with children’s age [ 12 , 61 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…For instance, understanding children’s cues is a challenge caregivers face in infancy, before children develop language. This perspective is consistent with evidence on the drivers of VAC in Colombia, which indicates that the risk of experiencing VAC varies with children’s age [ 12 , 61 ].…”
Section: Resultssupporting
confidence: 89%
“…Global research, including reviews [ 7 , 59 , 60 ] and cross-cultural studies [ 61 , 62 ], showed that multiple factors at the individual, family, community, and society levels predict VAC. Some of these factors include caregivers’ beliefs that children need physical punishment to be raised properly, caregivers’ mental health and self-regulation skills, caregivers’ own exposure to physical punishment in their childhood, low caregiver education, lower socioeconomic status, living in a violent context, living in rural vs. urban areas, and gender inequity, among others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key belief among mothers at high risk for using punishment is that physical punishment is necessary and instrumental for achieving parental goals [ 33 ]. Furthermore, data from 65 countries found that the caregiver’s belief that physical punishment was needed for a child to be raised properly was associated with the largest odds of spanking (Odds Ratio = 2.55, p < 0.001) [ 34 ]. Throughout the literature, supportive attitudes toward physical punishment are consistently associated with an increased likelihood of its use [ 30 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…One barrier to understanding co-occurrence in LMICs is that most high quality, national data on violent discipline come from UNICEF-supported Multiple Indicator Cluster Surveys (MICS) [ 28 ], which do not usually measure IPV prevalence. As a result, the growing number of multi-country analyses of MICS data have not included child exposure to IPV as a potential risk factor in research on violent discipline [ 29 36 ]. Conversely, most national surveys that measure IPV against women do not measure child discipline, with some exceptions, including the surveys in this study.…”
Section: Introductionmentioning
confidence: 99%